Using SCC Antigen and CRP Levels as Prognostic Biomarkers in Recurrent Oral Cavity Squamous Cell Carcinoma - Chen, I-How; Liao, Chun-Ta; Wang, Hung-Ming; Huang, Jung-Ju; Kang, Chung-Jan; Huang, Shiang-Fu (PloS one, 2014)
Squamous cell carcinoma antigen (SCC-Ag) and C-reactive protein (CRP) levels have been successfully used to stratify risk groups in primary oral squamous cell carcinoma (OSCC) patients; however, related biomarkers have rarely been investigated in recurrent OSCC. The purpose of the present study was to analyze the relationships of SCC-Ag and CRP levels at the time of recurrence with clinical factors and prognosis. We retrospectively recruited patients with recurrence in a cohort of 534 OSCC patients between March 2001 and July 2013. One hundred patients had recurrence. The serum SCC-Ag and CRP levels were measured at the time of cancer diagnosis, 3 to 6 months after treatment with clinical disease-free, and at the time of recurrence. The SCC-Ag levels were significantly lowered after treatment (paired t-test: p = 0.001) and re-elevated at the time of recurrence (paired t-test: p = 0.027). An SCC-Ag level ≥2.0 ng/ml and a CRP level ≥5.0 mg/L at the time of recurrence were significantly associated with recurrent tumor status (P<0.001), recurrent nodal metastasis (χ2 trend test: P = 0.020), distant metastasis (P<0.001), and overall survival (P<0.001). Moreover, the influence of both elevated SCC-Ag and CRP levels on overall survival (P<0.001, H.R. [95% CI]: 5.406 [2.210-13.222]) still existed after adjusting for the recurrent tumor stage and patient age. The present study demonstrates that concurrent high levels of both SCC-Ag and CRP at the diagnosis of recurrence acts as a predictor of recurrent tumor status, recurrent advanced tumor stage, distant metastasis, and survival after the diagnosis of recurrence. This study expands the applicability of these two markers in the risk stratification in recurrent OSCC.